2012
DOI: 10.1186/1897-4287-10-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing receptivity to future screening options for pancreatic cancer in those with and without pancreatic cancer family history

Abstract: BackgroundPancreatic cancer (PC) is considered the most lethal cancer and approximately 10% of PC is hereditary. The purpose of the study was to assess attitudes of at-risk family members with two or more relatives affected with pancreas cancer (PC) toward PC risk and future screening options.MethodsAt-risk family members and primary care controls were surveyed regarding perceived PC risk, PC worry/concern, attitude toward cancer screening, screening test accuracy, and intentions regarding PC screening via blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
(39 reference statements)
0
20
0
Order By: Relevance
“…Within this sample, participants described a psychosocial response to living with familial pancreatic cancer risk, such as worry and fear, which has been reported in previous literature [ 24 ]. These psychological responses were not constant, occurred over the course of the individual’s life, and were present during times that caused the person to remember familial experiences with PancCa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this sample, participants described a psychosocial response to living with familial pancreatic cancer risk, such as worry and fear, which has been reported in previous literature [ 24 ]. These psychological responses were not constant, occurred over the course of the individual’s life, and were present during times that caused the person to remember familial experiences with PancCa.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature supports that at risk individuals are willing to take part in pancreatic cancer risk reduction and screening interventions [ 24 ], [ 26 ]. Our findings present background as to why participants may be receptive to these interventions and demonstrate the salience of family experience on influencing health choices.…”
Section: Discussionmentioning
confidence: 99%
“…Screening participants who are FPC kindred commonly express grief from the experience of family death due to PC[ 128 - 130 ], and are distressed by the high mortality and uncertainty related to prevention and early detection[ 128 ]. Their motivation for participating in surveillance is " possible early detection of (a precursor stage of) PC " (95%-100%)[ 131 ], and they want to control their cancer risk by seeking information and resources to prevent PC[ 128 ].…”
Section: Surveillance Of High Risk Individualsmentioning
confidence: 99%
“…Their motivation for participating in surveillance is " possible early detection of (a precursor stage of) PC " (95%-100%)[ 131 ], and they want to control their cancer risk by seeking information and resources to prevent PC[ 128 ]. Research conducted by the Mayo Clinic indicated that 67% (238/361) of FPC kindred felt they had a higher lifetime risk of PC when compared to people of the same age, race, and gender, and 95% were likely to undergo blood test surveillance and 75% were likely to undergo EUS surveillance[ 130 ]. A study at the University of Toronto revealed that the perception of PC risk was higher in FPC kindred than in BRCA2 mutation carriers (42% vs 15%)[ 129 ].…”
Section: Surveillance Of High Risk Individualsmentioning
confidence: 99%
“…Additional studies have been performed to evaluate the overall experience reported by individuals living with the knowledge that they are at increased risk of pancreatic cancer, 106,111 their knowledge of pancreatic cancer screening, 112 and their receptivity 113 or intent to engage in pancreatic cancer screening. Two qualitative studies focusing on patient experiences with pancreatic cancer risk 111 and understanding of and intent to engage in pancreatic cancer screening 112 found the family experience was an important factor in how someone viewed their own risk for pancreatic cancer and became motivated to engage in invasive screening.…”
Section: Hereditary/familial Pancreatic Cancermentioning
confidence: 99%